HUBUNGAN KONDISI FISIK TERHADAP PRESTASI ATLET DAYUNG JAWA BARAT PON PAPUA 2021 - Amrul Hayat (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2021)
The aim of this research is to find out how much physical condition (power, endurance and strength) is related to the performance of West Java rowing athletes at PON Papua 2021. The population of this research is all canoing and TBR rowing athletes at West Java PON Papua 2021. The instrument used is observation. tests and measurements of physical condition abilities. The analysis technique is a correlational method. Based on the results of data analysis and discussion, the author obtained conclusions that can be drawn from research regarding the influence of power, endurance and strength on the performance of West Java rowing athletes at the 2021 Papua PON. The research results show that the significance value of each variable, namely power (X1), is Sig. 0.52 > 0.05, which means there is no relationship between power and the performance of West Java rowing athletes at PON Papua 2021, endurance (X2) is Sig. 0.01 < 0.05, which means there is a relationship between endurance and the performance of West Java rowing athletes at PON Papua 2021, strength (X3) is Sig. 0.21 > 0.05, which means there is no relationship between strength and the performance of West Java rowing athletes at PON Papua 2021 and simultaneously or jointly the Sig value. 0.049 < 0.050, which means that there is a relationship between physical condition and the performance of West Java rowing athletes at PON Papua 2021.